Faktor resiko yang berhubungan dengan terjadinya rupture perineum pada ibu bersalin - Silaban, Titin (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Rupture perineum is the occurrence of perineal tears when a baby is born naturally or spontaneously or using tools or procedures. The incidence of perineal rupture in birthing mothers in the world in 2020 was 2.7 million cases, where this figure is estimated to reach 6.3 million in 2050. On the Asian continent alone, 50% of mothers in labor experienced perineal rupture.4 Based on data from the Indonesian Ministry of Health In 2019, there were 4,221 maternal deaths in Indonesia, with most deaths caused by bleeding. In 2017, it was discovered that 75% of mothers who gave birth vaginally experienced perineal rupture. The aim of this research was to determine the relationship between maternal age, birth weight and parity with the incidence of perineal rupture. The population in this study were all mothers giving birth at PMB. Bdn. Ria Permata Sari, S.Keb, this type of research uses secondary data. Statistical test using testchi-square. The results of the univariate analysis showed that there were 17 respondents with perineal rupture (%), 25 respondents with normal birth weight (62.5%), 21 respondents (62.5%) who were not at risk, 18 respondents of primary and multiparous parity. respondents (45%). Based on statistical test resultschi-squareage obtainedp-value of 0.361, the birth weight of the baby is obtainedp-value 0.024, parity obtainedp-value of 0.020, meaning there is a significant relationship between parity and the incidence of perineal rupture. The conclusion is that there is a relationship between birth weight, parity and no relationship between maternal age and the incidence of perineal rupture in mothers. It is hoped that this research will provide information that can reduce or prevent the incidence of perineal rupture.